2022
DOI: 10.1080/15384101.2022.2155016
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate protects against hepatic ischemia-reperfusion injury by alleviating ferroptosis via the NRF2/SLC7A11/HO-1 axis

Abstract: Dimethyl fumarate (DMF), a therapeutic agent for relapsing-remitting multiple sclerosis, has cytoprotective and antioxidant effects. Ferroptosis, a pathological cell death process, is recently shown to play a vital part in ischemia-reperfusion injury (IRI). This study aimed to unveil the suppressive role of DMF on ferroptosis in liver IRI. The anti-ferroptosis effect of DMF on hepatic IRI was investigated using a liver IRI mouse model and a hypoxia-reoxygenation injury (HRI) model in alpha mouse liver (AML12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition to HIFs, NRF2, the master regulator of oxidative stress signaling, also plays an important role in hypoxia-induced ferroptosis. Many studies reported that NRF mediates the regulation of ferroptosis induced by hypoxia or H/R [ 124 , 125 , 128 , 138 ], while another group of studies reported that targeting NRF2 could inhibit hypoxia-or H/R-induced ferroptosis [ 149 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to HIFs, NRF2, the master regulator of oxidative stress signaling, also plays an important role in hypoxia-induced ferroptosis. Many studies reported that NRF mediates the regulation of ferroptosis induced by hypoxia or H/R [ 124 , 125 , 128 , 138 ], while another group of studies reported that targeting NRF2 could inhibit hypoxia-or H/R-induced ferroptosis [ 149 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…From understanding the mechanism involved in the inhibition of ferroptosis caused by hypoxia, avoiding the ferroptosis inhibition caused by hypoxia could be a new strategy for treating tumors with ferroptosis inducers [ 180 , 181 ]. Considering that ferroptosis is the major reason for IRI, many drugs have been developed to inhibit hypoxia-induced ferroptosis based on its mechanism [ 129 , 140 , 141 , 150 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ]. Intriguingly, hypoxia is a symptom of the Coronavirus Disease-2019 (COVID-19); HIF-1α plays an important role in the early phase of SAR-CoV-2 infection and is also associated with secondary organ damage [ 182 , 183 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil membrane-coated taurine nanoparticles increased the expression of SLC7A11 and GPX4, and decreased the expression of Ptgs2, suggesting that nano-taurine has a targeted therapeutic effect on hepatic I/R injury by inhibiting inflammation, oxidative stress and ferroptosis [ 417 ]. Dimethyl fumarate (DMF), a therapeutic agent utilized in the treatment of relapsing–remitting multiple sclerosis, demonstrates inhibitory effects on ferroptosis through activation of the NRF2/SLC7A11/HO-1 axis, thereby conferring protection against hepatic I/R injury [ 418 ]. Although the relationship between hepatic I/R injury and ferroptosis has been confirmed, the development and application of therapies and drugs targeting ferroptosis are still limited.…”
Section: Ferroptosis In Pathologiesmentioning
confidence: 99%
“…In addition, DMF inhibits the migration of immune cells across brain endothelial cells [ 26 ]. DMF has shown potential favorable effects in a range of diseases, such as hepatic ischemia-reperfusion injury [ 27 ], lymphoma [ 28 , 29 ], and inflammatory bowel disorders [ 30 ]. This medicine was also approved for the treatment of multiple sclerosis and psoriasis in the clinic [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%